Additional bryophytes from Nahanni National Park and vicinity, Northwest Territories, Canada - Steere, William C.; Scotter, George W. (Canadian Journal of Botany, 1978)
Additional fieldwork in Nahanni National Park and vicinity has added 91 species of bryophytes to the flora of that region. Twenty of these are new to the District of Mackenzie, and 37 are new to the Northwest Territories of Canada. Three species, Barbula coreensis (Card.) Saito, B. maxima Syed & Crundw., and B. perobtusa (Broth.) Chen are new to North America.